2015
DOI: 10.2903/sp.efsa.2015.en-774
|View full text |Cite
|
Sign up to set email alerts
|

Survey on sterigmatocystin in food

Abstract: A total of 1 259 samples of cereal grains, cereal products, beer and nuts were analysed for the presence of the mycotoxin sterigmatocystin. Samples were mainly collected at processing plants, storage facilities, wholesale and retail between August 2013 and November 2014, in nine European countries (mostly Greece, Italy, the Netherlands and the United Kingdom (UK), additionally in Cyprus, Germany, Latvia, Lithuania, and Poland). The products originated from 27 European countries and 18 other countries (mostly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…In a recent European survey on STC occurrence in cereals, rice was clearly identified as the product with the highest incidence of contamination [26]; we collaborated in that study and found that all paddy rice samples grown in Italy during 2013 ( n = 13) were contaminated (similar results were obtained for paddy rice from other countries). In that limited survey, the average contamination and the median were 0.89 and 0.76 μg·kg −1 , respectively; the STC level was higher than 1.0 μg·kg −1 in 38.5% of the samples and the maximum value was 1.9 μg·kg −1 .…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In a recent European survey on STC occurrence in cereals, rice was clearly identified as the product with the highest incidence of contamination [26]; we collaborated in that study and found that all paddy rice samples grown in Italy during 2013 ( n = 13) were contaminated (similar results were obtained for paddy rice from other countries). In that limited survey, the average contamination and the median were 0.89 and 0.76 μg·kg −1 , respectively; the STC level was higher than 1.0 μg·kg −1 in 38.5% of the samples and the maximum value was 1.9 μg·kg −1 .…”
Section: Resultssupporting
confidence: 67%
“…Successively, the results of a survey on STC in food highlighted that STC was rarely present in cereal grains and cereal products (limit of quantification of 0.5 μg·kg −1 ), except paddy rice and derived products [26]; in fact, all paddy rice samples ( n = 28), mainly originating from Italy and Greece, were contaminated with STC. Contamination of rice with STC has already been reported [27,28,29,30]; however, the number of analysed samples was low and high limits of quantification were often reported.…”
Section: Introductionmentioning
confidence: 99%
“…In cereal grains, STC was detected in 2%–6% of the wheat, rye, maize, and barley samples, mostly at levels < 1.5 μg/kg. A higher incidence and higher levels of contamination (14 samples, 1.5–6 µg/kg; 1 sample, 33 µg/kg) were observed in rice (in virtually all unprocessed rice and 21% of processed rice from the EU) and oats (22%) [21]. Sorghum is also commonly detected with STC contamination.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment of data collection, it may not be clear which foods contribute most to the exposure, samples may not be well characterised, analytical reference standards or reference materials are lacking, method of analysis may not be harmonised or validated, LOQs required to exclude potential health risks are unknown (Mol et al, 2015), and the relation between intake and excreted metabolites is unknown. Analysis of long-time stored duplicate or total diets may overcome these problems to some extent, assuming all relevant consumed foods are collected.…”
Section: Emerging Mycotoxinsmentioning
confidence: 99%
“…EFSA calculated a required LOQ of 1.5 µg/kg: based on consumption of the relevant food products, the level causing adverse effects in laboratory animals and the minimal required margin of exposure for genotoxic carcinogens. A dedicated survey was subsequently performed at an LOQ of 0.5 µg/kg and sterigmatocystin was detected in 10% of the 1,259 samples, in most cases below 1 µg/kg (Mol et al, 2015). Besides the issue of low LOQs, another issue with certain mycotoxins is the high heterogeneity of the contamination which may result in a high uncertainty of the analysis results (higher than the measurement uncertainty of the analysis as such), but this clearly depends on the type of food product.…”
Section: Data Collection Studiesmentioning
confidence: 99%